Author Correction: Non-professional phagocytosis: a general feature of normal tissue cells (Scientific Reports, (2019), 9, 1, (11875), 10.1038/s41598-019-48370-3) - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-06-16

Non-professional Phagocytes can phagocytize Necrotic Cells at any Stage of the Cell Cycle - Hofmann, Andrea; Seeberg, Jacob; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27